2011
DOI: 10.1021/om2000772
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of η1-α-Phosphinocarbene Complexes of Manganese and Mechanistic Insight into Their Base-Induced Transformations

Abstract: A series of η1-α-phosphinocarbene complexes of manganese, Cp(CO)2MnC(R)PR′R′′ (3; 3a: R = Ph, R′ = H, R′′ = Mes; 3b: R = Me, R′ = H, R′′ = Mes; 3c: R = Ph, R′ = R′′ = Ph; 3d: R = Ph, R′ = R′′ = N(i-Pr)2; 3e: R = Ph, R′ = Me, R′′ = Mes), was generated at low temperature upon nucleophilic addition of the primary phosphine H2PMes and secondary phosphines HPPh2, HP(N(i-Pr)2)2, or (±)-HPMeMes to the cationic carbyne complexes Cp(CO)2Mn+C−R ([1]+; [1a]+: R = Ph; [1b]+: R = Me), followed by deprotonation of the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 92 publications
1
8
0
Order By: Relevance
“…We first observed that the Mn I phosphoniocarbene complex [MpC(Me)PPh 2 H]BCl 4 [ 2 a ]BCl 4 (here and thereafter, Mp=Cp(CO) 2 Mn) generated in situ upon addition of PPh 2 H to the methylcarbyne precursor [MpCMe)]BCl 4 , [ 1 Me ]BCl 4 at low temperature,1b,d,e can uptake a second molecule of phosphine to give the cationic complex [ 4 aa ‐ H ]BCl 4 featuring a newly formed pendant PCP structural motif containing ligand resulting formally from the coupling of the carbyne fragment and two secondary phosphines (Scheme ). Deprotonation of the latter upon purification on an alumina column afforded a neutral diphosphine complex 4 aa in a nearly quantitative yield.…”
Section: Methodsmentioning
confidence: 99%
“…We first observed that the Mn I phosphoniocarbene complex [MpC(Me)PPh 2 H]BCl 4 [ 2 a ]BCl 4 (here and thereafter, Mp=Cp(CO) 2 Mn) generated in situ upon addition of PPh 2 H to the methylcarbyne precursor [MpCMe)]BCl 4 , [ 1 Me ]BCl 4 at low temperature,1b,d,e can uptake a second molecule of phosphine to give the cationic complex [ 4 aa ‐ H ]BCl 4 featuring a newly formed pendant PCP structural motif containing ligand resulting formally from the coupling of the carbyne fragment and two secondary phosphines (Scheme ). Deprotonation of the latter upon purification on an alumina column afforded a neutral diphosphine complex 4 aa in a nearly quantitative yield.…”
Section: Methodsmentioning
confidence: 99%
“…The method exemplified in the case of manganese shows a high tolerance regarding the nature of substituents of both carbyne complex 55 and phosphine (Scheme ). The deprotonation of α‐phosphoniocarbene complexes 56 derived from primary and secondary phosphines constitute an elegant entry for the preparation of the corresponding phosphinocarbene complexes 57 ,…”
Section: Phosphoniocarbenesmentioning
confidence: 99%
“… Preparation of Mn I complexes 56 and 57 of acyclic phosphonio‐ and phosphinocarbenes, respectively ,…”
Section: Phosphoniocarbenesmentioning
confidence: 99%
“…Additionally, monocarbonyl acyl anion 96A reacted with iodine to afford a thermally unstable η 3 -phosphinoketene complex [Cp(CO) 2 Mn(η 3 -C(O)C-(Ph)PIMes)], which upon warming to room temperature rearranged into the η 1phosphaalkene complex [Cp(CO) 2 Mn(η 1 -P(Mes)�C(I)-Ph)]. 97 Lugan and Valyaev described the syntheses and reactivities of manganese methylene phosphonium complexes 101A-B. Their precursor was obtained from Fischer carbene 97 and Hunig's base.…”
Section: Tungstenmentioning
confidence: 99%
“…Addition of traces of water to a solution of 95A in THF results in its immediate and quantitative isomerization ( 96B ; for all reactions see Scheme ). Additionally, monocarbonyl acyl anion 96A reacted with iodine to afford a thermally unstable η 3 -phosphinoketene complex [Cp(CO) 2 Mn(η 3 -C(O)C-(Ph)PIMes)], which upon warming to room temperature rearranged into the η 1 -phosphaalkene complex [Cp(CO) 2 Mn(η 1 -P(Mes)C(I)Ph)] …”
Section: Synthesis Of D-block Element Phosphaalkene Complexesmentioning
confidence: 99%